Hadith on Neighborly Conduct and Bugis Ethical Values: An Anthropological Reading of Sipakatau, Sipakalebbi, and Sipakainge’ - Muhammad Sabir; Ibrahem Narongrasakhet; Andi Mujahidil Ilman SM; Zulfahmi Alwi; Ahmad Jamin; Zikri Darussamin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
Hadith studies in the Indonesian archipelago have predominantly focused on normative, legal and theological dimensions, while the literary and cultural reception of hadith within local traditions remains underexplored. This study investigates how prophetic teachings on neighborly conduct are mediated, interpreted and embodied within Bugis cultural practice, with particular reference to the Pau-Paunna Budisettihara manuscript. Drawing on selected hadiths concerning neighborly ethics and passages from the Pau-Paunna Budisettihara manuscript, this study employs a qualitative, library-based approach through a Systematic Literature Review (SLR), informed by the anthropology of hadith and Jauss's Reception of Religious Texts theory. The hadiths examined include those commanding people to speak good, honor their neighbors, and respect guests, analyzed with textual passages that embody the values of sipakatau (humanizing others), sipakalebbi (mutual respect), and sipakainge' (mutual moral reminder). The findings reveal that hadiths on neighborly conduct are not merely understood theologically but are deeply internalized within Bugis social practices that emphasize harmony, dignity, reciprocity and social solidarity. This study contributes to contemporary hadith scholarship by demonstrating the applicability of reception theory in hadith studies and by advancing an interdisciplinary framework that integrates hadith studies, anthropology, and local cultural wisdom in understanding living hadith within the Indonesian context.